Pemanfaatan Pati Sagu pada Pembuatan Kapsul dengan Penambahan Gliserol - Febby Jeanry Polnaya; Milian Tengker; Vita Novalina Lawalata (Jurnal Teknologi Hasil Pertanian, 2023)
The purpose of this study was to determine the effect of several concentrations of glycerol in the manufacture of capsules from sago starch phosphate. Edible film testing includes physical, mechanical, and barrier film properties, while capsule testing includes moisture content, disintegration time, and dissolution. The design used was a completely randomized design consisting of a non-factorial with three levels of glycerol concentration (15, 25, and 35%, v/v). Variables measured were thickness, transparency, tensile strength and elongation, water vapor transmission rate, moisture content, disintegration, and dissolution. The results showed that the glycerol affects the starch molecule’s bond thereby increasing the rate of thickness, elongation, water vapor transmission rate, moisture content, disintegration, and dissolution, even while can decreasing the tensile strength. The concentration of 15% glycerol showed the best results compared to other concentration treatments.